Electronic multilingual terminological dictionary in teaching business languages - Kovalchuk, Olga (My University, 2013)
The theses present the notion of an electronic multilingual terminological dictionary and the prospects for its use in teaching a foreign language
Keywords: electronic dictionary; business language; електронний словник; ділова іноземна мова; электронный словарь; деловой иностранный язык; кафедра ділової іноземної мови та міжнародної комунікації